Changes in Mortality in Pakistan 1960-88 (The Pakistan Development Review, 1991)
The relatively high levels of mortality in Pakistan compared to the rest of the Asian region, particularly countries like Sri Lanka and China, have kept population growth rates in check. However, on the other hand, persistently high levels of infant-child mortality are more than often argued to be a strong factor working against a fertility decline in Pakistan. It is without doubt that bringing about further mortality declines is most definitely desirable and government policy has addressed this issue. However, the major thrust of official effort in the past few decades has been towards the curtailment of high fertility levels.